Analisis Penggunaan Video Animasi Nussa dan Rara dalam Menstimulasi Kemampuan Empati Anak Usia 4-5 Tahun di TK Negeri Pembina Pandeglang - Naiya Fadhillah; Atin Fatimah; Luluk Asmawati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to analyze the use of the Nussa and Rara animated video in stimulating the empathy skills of children aged 4–5 years at TK Negeri Pembina Pandeglang. The study employed a descriptive qualitative approach, with data collected through observation, interviews, documentation, and field notes. The findings revealed that the implementation of the Nussa and Rara animated video was carried out systematically through three stages: planning, implementation, and evaluation. The planning stage included preparing the Daily Learning Implementation Plan (RPPH), selecting video episodes containing empathy-related values, and organizing instructional materials. During the implementation stage, the animated videos were shown once or twice a week for approximately five minutes under teacher guidance. The evaluation stage involved discussions, question-and-answer sessions, and positive reinforcement to strengthen children's understanding. The use of the Nussa and Rara animated video successfully stimulated three dimensions of children's empathy: cognitive empathy, reflected in the ability to understand others' feelings; affective empathy, demonstrated by the ability to share and experience others' emotions; and behavioral empathy, shown through concrete actions such as sharing food, cooperating to tidy up toys, and inviting lonely peers to play together. The selection of the Nussa and Rara animated video was based on its positive role models, age-appropriate storylines for children aged 4–5 years, engaging visual presentation, adequate audiovisual facilities, and relevance to children's daily lives. However, several challenges remained, including differences in children's verbal abilities and limited parental support. These challenges were addressed by selecting shorter video episodes, using simple guiding questions, and implementing active and creative learning strategies. Therefore, the Nussa and Rara animated video can serve as an effective educational medium for stimulating empathy skills in early childhood.